Group counseling for students transitioning out of postsecondary education - Lane, Joel A. (Groupwork, 2013)
This paper proposes a narrative-based group counseling model for postsecondary students preparing to graduate and transition out of university life. The challenges associated with this transition are both psychological and career-related in nature. The author utilizes multiple transition frameworks to provide a conceptualization of the graduation transition, and offers an overview of narrative therapy, its use in transition counseling, and its use in groupwork. The proposed intervention calls for two facilitators and between six and eight members. An intervention overview is provided that includes recruitment and prescreening instructions as well as content for eight sessions.